PENGARUH KARAKTERISTIK PEMERINTAHAN TERHADAP AUDIT DELAY LAPORAN KEUANGAN PEMERINTAH DAERAH - Baldric Siregar (Jurnal Riset Akuntansi dan Keuangan, 2015)
Financial statements that were not provided on time may cause those report loses their capacity toinfluence decisions. This study aimed to examine the effects of local government characteristics onaudit delay of government financial reports of Yogyakarta Special Region and Central Java. Thisstudy uses 40 districs and cities as the study sample. Data were obtained from the Supreme AuditAgency and the Central Bureau of Statistics. The dependent variable of this research is audit delay.While the independent variables include the size of government, the value of the budget, and leverage.Multiple regression analysis was used to test the hypothesis. The test results showed that the size ofgovernment and the level of leverage negatively affect audit delay. Budgets value does notsignificantly affect audit delay.Keywords: audit delay, financial report, governmental size, budget value, and leverage